Європейський суд з прав людини як міжнародно-правова гарантія захисту прав і свобод громадян України - Магновський, Ігор; Mahnovskyi, Igor; Магновский, Игорь (Видавництво Львівської політехніки, 2017)
У правовому аспекті висвітлено Європейський суд з прав людини у ракурсі міжнародно-правової гарантії захисту прав і свобод громадян України. З’ясовано правові підстави поширення юрисдикції Європейського суду з прав людини на Україну та процедуру виконання нею його рішень. Окреслено місце та роль Європейського суду з прав людини в конституційно-правовому механізмі захисту прав і свобод громадян України. Визначено проблемні питання виконання рішень та застосування практики Європейського суду з прав людини в Україні. Охарактеризовано особливості умов прийняття скарг у Європейський суд з прав людини. Обґрунтовано пропозиції щодо вдосконалення механізму виконання рішень та застосування практики Європейського суду з прав людини в Україні, що є невід’ємним фактором сучасної конституційно- правової політики української держави у сфері забезпечення прав і свобод її громадян.

The article highlights the legal aspect of the European Court of Human Rights in the perspective of international legal guarantees of protection of rights and freedoms of citizens of Ukraine. It is found legal grounds of spreading jurisdiction of the European Court of Human Rights in Ukraine and the procedure for the fulfillment of its decisions. Outlined the place and role of the European Court of Human Rights in the constitutional-legal mechanisms for protection of rights and freedoms of citizens of Ukraine. Identified issues of enforcement and application of the European Court of Human Rights in Ukraine. Characterized conditions of complaints to the European Court of Human Rights. Grounded suggestions for improving the mechanism for enforcement and application of the European Court of Human Rights in Ukraine, which is an essential factor in modern constitutional-legal Ukrainian state policy in the sphere of rights and freedoms of its citizens. Due to the importance and significance enforcement and application of the European Court of Human Rights appears necessary to consolidate the constitutional level relevant legal norms binding on its solutions for domestic law Ukraine. Congregation that international-law guarantees encourage to implementation of the necessary legal status of citizens of Ukraine transition from provided in the Constitution and laws of the State the possibility to reality. It notes that the legal guarantees of rights and freedoms of person and citizen, as intra-law and international law are in tight close connection between themselves, are interdependent, interrelated and complementary to each other and act as a key component of the Remedies Ukraine and freedoms.

В статье в правовом аспекте освещены Европейский суд по правам человека в ракурсе международно-правовой гарантии защиты прав и свобод граждан Украины. Выяснены правовые основания распространения юрисдикции Европейского суда по правам человека в Украине и процедуру выполнения его решений. Определены место и роль Европейского суда по правам человека в конституционно-правовом механизме защиты прав и свобод граждан Украины. Определены проблемные вопросы выполнения решений и применение практики Европейского суда с прав человека в Украине. Охарактеризованы особенности условий принятия жалоб в Европейский суд по правам человека. Обоснованы предложения относительно совершенствования механизма исполнения решений и применение практики Европейского суда по правам человека в Украине, что является неотъемлемым фактором современной конституционно-правовой политики украинского государства в сфере обеспечения прав и свобод её граждан.
European court of human rights as an international legal guarantee of the rights and freedoms of citizens of Ukraine
Европейский суд по правам человека как международно-правовая гарантия защиты прав и свобод граждан Украины
Keywords: Європейський суд з прав людини; Європейська Конвенція з прав людини; міжнародно-правова гарантія; права і свободи людини та громадянина; юридичні гарантії; European Court of Human Rights; the European Convention on Human Rights; international legal guarantee; of the rights and freedoms of man and citizen; legal guarantees; Европейский суд по правам человека; Европейская Конвенция по правам человека; международно-правовая гарантия; права и свободы человека и гражданина; юридические гарантии; 342.72